2013
DOI: 10.1177/0192513x13490933
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure History and Teenage Cohabitation

Abstract: This study uses data from the first three waves of the National Longitudinal Study of Adolescent Health, from 8,019 adolescents and their mothers, to examine links between multiple dimensions of family structure and instability over adolescents’ life courses, family functioning, peer contexts, and teenage cohabitation. Investigated explanations include an instability model, socioeconomic-stress model, and intergenerational transmission. Results from logistic regression models link single-mother and stepfamily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
(98 reference statements)
0
13
0
Order By: Relevance
“…Previous research on special populations such as children, adolescents, and immigrants showed that family function had a protective effect on mental health [810, 40]. The present study confined such protection effects to the adult population.…”
Section: Discussionmentioning
confidence: 75%
“…Previous research on special populations such as children, adolescents, and immigrants showed that family function had a protective effect on mental health [810, 40]. The present study confined such protection effects to the adult population.…”
Section: Discussionmentioning
confidence: 75%
“…This distinction may be explained by patterns of prior family instability leading to specific family structures in adolescents’ homes (Fomby and Bosick, 2013), or by caregiving practices, family dynamics, and attachment patterns that may differ by family structure type irrespective of subsequent transitions (Dolbin-MacNab and Keiley, 2009; Langton and Berger, 2011; Shin et al, 2010). The lack of significant findings associated with household composition change may reflect variation in family processes and dynamics implicated in healthy child and youth development that differ by family structure (Morrissey, 2008; Vanassche et al, 2014; Zito, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Three studies found mediation for some of the transitions or some of the outcomes but not all (Bachman et al, 2012;Sun & Li, 2008;Vargas, Roosa, Knight, & O'Donnell, 2013). The overwhelming majority of the studies with family functioning and parenting mediating variables, however, found no evidence that these variables were mediators during adolescence (Bachman et al, 2009;Krohn, Penly Hall, & Lizotte, 2009;Langenkamp & Frisco, 2008;Schroeder et al, 2010;Shaff et al, 2008;Walper et al, 2015;Zito, 2015;Zito & De Coster, 2016). Finally, no studies suggested that parent functioning was a consistent mediator: Bachman et al (2012) found that parents' psychological distress was a mediator only for cohabiting relationships lasting at least 2 years; and neither Bachman et al (2009) nor Zito (2015 found any mediation effect by parent functioning.…”
Section: Child Characteristicsmentioning
confidence: 99%
“…Following Wu and Martinson's (1993) groundbreaking study-and subsequent research examining the influence of transitions on sexual behavior (Wu, 1996;Wu & Thomson, 2001)- Fomby and Cherlin (2007) were the first to directly test the instability and selection hypotheses against each other in a large, representative sample. They formalized the two explanatory theories and compared them with a broader range of potential outcomes (cognitive achievement, externalizing behavior, and delinquent behavior).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation